Eco-Pesantren as A Basic Forming of Environmental Moral and Theology - Herdiansyah, Herdis; Sukmana, Hadid; Lestarini, Ratih (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2018)
The rising of education with an environmentally friendly approach becomes one of the focuses on implementing sustainable growth of social life. This principle includes an attempt to develop the ecologically friendly pesantren. Along the time, pesantren is identified as a religion and social center. Meanwhile, its surrounding environment has not become the primary priority. This paper sought to analyze the activity of community service related to initiating the perspective change of pesantren. The study implies that pesantren not only an education institute practicing educational activity, but also become an agent of change for creating a better social life and society around, and further, to perform the environmentally friendly pesantren. The research used the literature review approach to propose the Eco-Pesantren strategy, the benefits and social-economic impact for pesantren and the greater community. Moreover, the Eco-Pesantren concept becomes the basis and good characteristic learning with concern for the environment. Furthermore, environmental theology brings Eco-Pesantren on the profound philosophy of eco-ethical perspectives.